Images in Medical Practice - Siddiqui, Md Mahmudur Rahman; Hossain, Ahmed; Rahman, Md Yousuf Ur; Islam, Quazi Tarikul (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v28i2.5375 J Bangladesh Coll Phys Surg 2010; 28: 128